Medical honey for canine nasal intertrigo: A randomized, blinded, placebo-controlled, adaptive clinical trial to support antimicrobial stewardship in veterinary dermatology. - Gabrielle Brosseau; Nadia Pagé; Caroline de Jaham; Jérôme R E Del Castillo (PLoS ONE)
Intertrigo is a skin fold dermatitis often requiring recurrent treatment with topical antiseptics or antibiotics, which can select antimicrobial resistance. To minimize this risk, we tested the effectiveness of medical-grade Manuka honey at treating intertrigo as compared to a placebo hydrogel. We additionally characterized the culturable microbial flora of intertrigo and recorded any adverse effect with either treatment. During this randomized, placebo-controlled, double-blinded, adaptive group-sequential trial, the owners washed the affected sites on their dog with water, dried and applied a thin film of either the honey or the placebo product once daily for 21 days. Cytological and lesional composite scores, owner-assessed pruritus, and microbial cultures were assessed prior to treatment and on Day-22. The fixed effects of time, treatment, and animal-related variables on the pruritus and on each composite score, accounting for random dog effect, were estimated separately with generalized linear mixed models for repeated count outcomes (α = 0.05). The null hypothesis of equal treatment effects was rejected at the first interim analysis. The placebo (n = 16 dogs) outperformed the medical honey (n = 13 dogs) at improving both the cytological score (Treatment×Time = -0.35±0.17; P = 0.04) and clinical score (Treatment×Time = -0.28±0.13; P = 0.04). A microbial burden score higher than 4 increased the severity of the cytological score (dichotomous score: 0.29±0.11; P = 0.01), which in turn increased the severity of the clinical score and pruritus score. For every unit increase in cytological score, the linear predictor of clinical score increased by 0.042±0.019 (P = 0.03), and the one of pruritus score increased by 0.12±0.05 (P = 0.01). However, medical honey outperformed the placebo at alleviating the dog's owner-assessed pruritus after statistically controlling for masking effects (Time = -0.94±0.24; P = 0.002; and Treatment×Time = 0.80±0.36; P = 0.04). Unilateral tests of the least-square mean estimates revealed that honey only significantly improved the pruritus (Hommel-adjusted P = 0.003), while the placebo only improved the cytological and clinical scores (Hommel-adjusted P = 0.01 and 0.002, respectively). Taken together, these results question the value of Manuka honey at treating nasal intertrigo in dogs.